Psychiatric aspects of hepatic encephalopathy, hepatitis C, and liver transplantation - Hůlková, Michaela; Hosák, Ladislav (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2009)
Psychiatric symptoms often accompany liver disease. The incidence of liver disease has increased recently among psychiatric patients. Hepatic encephalopathy, defined in broad terms as changes in neurological function resulting from liver disease, encompasses a wide range of neuropsychiatric signs and symptoms that are associated with both chronic and acute liver failure. Hepatic encephalopathy is associated with cognitive dysfunction, impairment of the quality of life, and higher incidence of road accidents. The incidence of viral hepatitis C has been increasing worldwide. It can cause general slowing of psychomotor performance, disorientation, depression or hypomania, personality disorders, or sleep disorders. Severe depression can be caused by treatment of hepatitis C with interferon alpha. Paroxetine and citalopram show the best proven results in a double-blinded placebo-controlled trials of prophylactic treatment for IFN-?–induced depression. Before liver transplantation, anxiety, depression and alexithymia are frequent; post-traumatic stress disorder, psychosis and depression (because of survivor guilt) may appear after liver transplantation. In post-transplantation anxiety, women perceive liver transplantation as a psychosocial stressor more than men do. Women also have a worse quality of life after liver transplantation than men.
Keywords: transplantace jater; mezioborová komunikace; financování organizované; nemoci jater; Hepatolenticular Degeneration; hepatitida C; Hepatitis C; Signs and Symptoms; Drug Therapy; duševní poruchy; Hepatic Encephalopathy; lidé; Immunosuppressive Agents; psychopatologie; příznaky a symptomy; rifamyciny; jaterní encefalopatie; farmakoterapie; Financing, Organized; hepatolentikulární degenerace; Liver Diseases; Liver Transplantation; Neomycin; medicína založená na důkazech; Psychopathology; Interdisciplinary Communication; Mental Disorders; Rifamycins; neomycin; ribavirin; imunosupresiva; Evidence-Based Medicine; Ribavirin; Humans